The Effect of Gender-Affirming Medical Care on the Vaginal and Neovaginal Microbiomes of Transgender and Gender-Diverse People - Krakowsky, Yonah; Potter, Emery; Hallarn, Jason; Monari, Bern; Wilcox, Hannah; Bauer, Greta; Ravel, Jacques; Prodger, Jessica L. (Frontiers in Cellular and Infection Microbiology, 2022)
Transgender and gender diverse individuals may seek gender-affirming medical care, such as hormone therapy or surgery, to produce primary and/or secondary sex characteristics that are more congruent with their gender. Gender-affirming medical care for transmasculine individuals can include testosterone therapy, which suppresses circulating estrogen and can lead to changes in the vaginal epithelium that are reminiscent of the post-menopausal period in cisgender females. Among transfeminine individuals, gender-affirming medical care can include vaginoplasty, which is the surgical creation of a vulva and neovaginal canal, commonly using penile and scrotal skin. The effect of gender-affirming medical care on the vagina of transmasculine individuals and on the neovagina of transfeminine individuals is poorly characterized. This review summarizes what is known of the epithelium and local microbiota of the testosterone-exposed vagina and the neovagina. We focus on potential pathogens and determinants of gynecological health and identify key knowledge gaps for future research.